Pengaruh Profitabilitas dan Likuiditas Terhadap Harga Saham di Perusahaan Manufaktur Yang Terdapat di Bursa Efek Indonesia (Sektor Makanan dan Minuman) - Anggun Enjelina Sirait; M Khoiri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study was to determine the effect of Profitability and Liquidity on Stock Prices in companies that have been listed on the Indonesia Stock Exchange (IDX) in the period from 2016 to 2020. In this study, there were 8 companies in the food and beverage sector that were sampled using purposive sampling method to determine the sample on certain conditions. Then the variables taken are Return On Assets, Current Ratio and stock prices. In this study using a quantitative approach and data collection was carried out using secondary data sources, namely collecting data on financial statements of sector and beverage companies listed on the Indonesian stock exchange which were collected indirectly from the object of research but obtained the data from other sources such as the internet and the company's official website. the. and data analysis using multiple linear regression analysis with the help of SPSS version 26 to process the data. The results shown by this study are that (1) partially the return on assets has a positive and significant effect on prices, the second (2) simultaneously the current ratio has a positive and significant effect on stock prices and the last (3) simultaneously return on assets and the current ratio has a positive and significant effect on stock prices